The subtle art of not giving a f*ck : a counterintuitive approach to living a good life - Manson, Mark (New York : Harper, an imprint of HarperCollins Publishers, 2016)
Offers blunt advice on how to focus on what truly matters by accepting limitations and letting go of the pursuit of constant positivity.
Includes bibliographical references.
Keywords: Conduct of life; Self-actualization (Psychology).; Happiness